Food Safety: Ready-to-Eat Foods - Jennifer Hillan; Amarat Simmone (EDIS)
This document provides guidelines for ensuring the safety of ready-to-eat fresh foods, which can pose a high risk for foodborne illness. It emphasizes selecting well-packaged, clean, and properly stored foods at the grocery store. First published: May 2010.